2015
DOI: 10.1159/000442024
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Impedance and Expression of Tight Junction Components of the Nasal Turbinate and Polyp

Abstract: Purpose: We investigated the electrical impedance and expression of tight junction components of the turbinate mucosa, nasal polyp, and normal skin. Procedures: The inferior turbinate and nasal polyp of patients with chronic rhinosinusitis and the postauricular skin of patients with otitis media were examined. Electrical impedance was measured in vivo using a tissue conductance meter. Expressions of claudin-1 and tricellulin were examined by fluorescence immunohistochemistry and quantitative RT-PCR. Results: E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…25 Another study revealed that the electrical impedance of skin, which was calculated from the values measured by this method, was higher than those of the nasal turbinate and nasal polyps and that claudin-1 mRNA levels paralleled electrical impedance values. 26 Although we did not evaluate the expression of tight junction proteins in this study, increased MA in patients with FD was likely caused by decreased expression of tight junction proteins, based on a previous study by Vanheel et al…”
Section: Discussionmentioning
confidence: 88%
“…25 Another study revealed that the electrical impedance of skin, which was calculated from the values measured by this method, was higher than those of the nasal turbinate and nasal polyps and that claudin-1 mRNA levels paralleled electrical impedance values. 26 Although we did not evaluate the expression of tight junction proteins in this study, increased MA in patients with FD was likely caused by decreased expression of tight junction proteins, based on a previous study by Vanheel et al…”
Section: Discussionmentioning
confidence: 88%
“…25 Another study revealed that the electrical impedance of skin, which was calculated from the values measured by this method, was higher than those of the nasal turbinate and nasal polyps and that claudin-1 mRNA levels paralleled electrical impedance values. 26 Although we did not evaluate the expression of tight junction proteins in this study, increased MA in patients with FD was likely caused by decreased expression of tight junction proteins, based on a previous study by Vanheel et al 17 …”
Section: Discussionmentioning
confidence: 88%
“…TNF, a complex and important inflammatory factor, induces local production of IgA and stimulates eosinophils, and it plays an important role in the pathogenesis of CRSwNP (Kato et al, 2008;Cho et al, 2015;Shimizu et al, 2016). The integrity of the airway epithelium is a prerequisite for its good barrier function, which depends on the intercellular junctions, including tight junctions and adhesion junctions (Suzuki et al, 2016;Jiao et al, 2018). Studies have shown that the breakdown of tight junctions and adhesion junctions of CRS and the decrease of protein component expression are major factors leading to the occurrence of CRS (Kim et al, 2018;Tian et al, 2018).…”
Section: Discussionmentioning
confidence: 99%